A Study on the impact of E-Education on Employment Opportunities - Sharma, Dr. (CA) Megha; Vyas, Ms. Aarti; Sharma, Dr. Aastha (The journal of contemporary issues in business and government, 2023)
The advancement of technology has revolutionized the traditional education system, leading to the rise of E-education. E-education is defined as the delivery of education and training through the use of electronic media, such as the internet, computers, mobile devices, and other digital tools. The purpose of this paper is to explore the impact of E-education on employment opportunities. The study includes a thorough review of the existing literature on the topic, along with empirical evidence from recent research studies. The findings indicate that E-education has a positive impact on employment opportunities, as it offers flexible learning options, facilitates skill development, and improves employability. However, the success of E-education in enhancing employment opportunities depends on several factors, including the quality of education, the credibility of the E- education provider, the relevance of the course to the job market, and the learner's motivation and self-discipline. The study concludes that E-education has the potential to bridge the gap between education and employment, particularly in the context of the digital age, where technology has become an integral part of the workforce.